Atividade de espécies vegetais ricas em triterpenos e polifenóis sobre o zika virus e investigação fitoquímica de Terminalia glabrescens e Maytenus ilicifolia. - Rosângela Santos Pereira (2022)
Zika virus (ZIKV) is an emerging arbovirus, whose infection in humans can lead to serious complications such as Guillain-Barré syndrome and congenital microcephaly. There are no vaccines or drugs to treat ZIKV infections, thus justifying the search for effective antivirals. In this context, the present work aimed to identify natural products with potential activity against ZIKV based on the screening of plant extracts and phytochemical study of some active extracts. Plant species were selected by a chemosystematic approach, prioritizing those rich in polyphenols, triterpenes, and steroids, classes of natural products reported to have anti-ZIKV or broad-spectrum antiviral activity. Thirty-seven plant extracts, eight selected compounds, and a mixture of friedelin-friedelinol were initially screened on ZIKV-infected Vero CCL-81 cells at non-cytotoxic concentrations (3, 10 and 30 µg/mL for the extracts and mixture; 3 and 10 µM for the compounds). About 35% of the extracts reduced viral load in a concentration dependent manner, namely, Maytenus ilicifolia (dichloromethane and methanol extracts), M. rigida, M. truncata, M. acanthophylla, Ouratea spectabilis, Baccharis calvescens, B. imbricata, B. magnifica, B. opuntioides, Terminalia glabrescens, T. phaeocarpa and Echinodorus grandiflorus. On the other hand, none of the assayed compounds inhibited ZIKV replication. Subsequently, the anti-ZIKV activity of the active extracts was evaluated at non-cytotoxic concentrations in human neuroblastoma SH-SY5Y cells and significant antiviral activity (ranging from 1.7 to 4.5 log inhibition of viral load) was obtained for E. grandiflorus, M. ilicifolia (dichloromethane extract), M. rigida, T. phaeocarpa and T. glabrescens. The median cytotoxic concentration (CC50, µg/mL) of 8 active extracts [M. rigida, M. truncata, E. grandiflorus, M. ilicifolia (dichloromethane and methanol extracts), B. calvescens, T. glabrescens and T. phaeocarpa] was determined in Vero CCL-81 and SH-SY5Y cells, being significantly higher in the first viral strain. The preliminary investigation of the mechanism of action of the eight active extracts in Vero CCL-81 cells was carried out. The extracts did not present a prophylactic effect and did not act in the step of internalization of the viral particle, suggesting other mechanisms of antiviral action. The median effective concentration (EC50, µg/mL) was determined in SH-SY5Y cells for the extracts of M. ilicifolia (EC50 =16.8 ± 10.3), T. phaeocarpa (EC50 =22.0 ± 6.8) and T. glabrescens (EC50 =20.4 ± 10.2), being obtained selectivity indexes (SI) of 3.4, 4.8, and 6.4, respectively. The active extracts of M. ilicifolia (dichloromethane extract) and T. glabrescens (ethanol extract) were dereplicated by UPLC-DAD-ESI-MS/MS, resulting in the identification of six triterpenes (ursolic and betulinic acids, friedelin, friedelinol, lupeol and amyrin) in the first and 27 phenolic compounds in the second. Both extracts were fractionated by silica gel column chromatography. The obtained n-hexane and dichloromethane fractions were analyzed by GCMS, which revealed similar chemical profiles and led to the identification of 11 compounds, comprising 7 esters, 1 alcohol, 1 triterpene and 2 hydrocarbons. The phytochemical study of T. glabrescens afforded three solids, whose analysis by conventional spectrometric methods (MS and 1D and 2D NMR) allowed their identification as glutinol, β-sitosterol, and a mixture of αand β-amyrin, of which only the second has been reported for the species. The phytochemical study of M. ilicifolia extract resulted in the isolation and identification of friedelan-3β-ol. The dichloromethane and ethyl acetate fractions of both species showed significant anti-ZIKV activity in Vero CCL-81 and SH-SY5Y cells. In its turn, β-sitosterol isolated from T. glabrescens (CC50 = >300 µM, CE50 = 71.27±7.08 µM, SI = 4.20) and friedelan-3β-ol isolated from M. ilicifolia (CC50 = >300 µM, CE50 = 58.23±19.85 µM and IS = 5.15) significantly reduced the viral load in ZIKV-infected SH-SY5Y cells. The obtained results highlight the potential of M. ilicifolia and T. glabrescens extracts as sources of anti-ZIKV compounds, especially triterpenes and sterols.